Port Mulgrave, Yakutat Bay, Alaska / drawn by H. Lindenkohl - United States Coast Survey (1875)
Depths shown by soundings. "Surveyed by W.H. Dall, Act'g. Assist. in May 1874." No. 752. Annotated 1:7,04